A participative network of organic and conventional crop farms in the Seine Basin (France) for evaluating nitrate leaching and yield performance. (October 2016) - Benoit, Marie; Garnier, Josette; Beaudoin, Nicolas; Billen, Gilles
Abstract: In the Seine Basin, characterized by intensive arable crops, most surface and groundwater is contaminated by nitrate (NO3 − ). A collaborative study was set up, involving a network of volunteer farmers, to investigate NO3 − leaching with ceramic cups (90 cm deep) on whole crop rotations of organic (OF) and conventional (CF) commercial farms in the Seine Basin. A total of eight CF and six OF systems were studied (63 fields) in five different soil and climate conditions, taking into account a wide diversity of practices (including low or no exogenous N inputs, systematic catch-crop implementation, and no tillage) and use of different exogenous organic matter (EOM) such as biogas residue; slurry; poultry manure; and cow and horse manure. Over the 2 years, OF cropping systems (including alfalfa) led to a lower average sub-root concentration (37 ± 9 mg NO3 − l − 1 ) than CF systems (48 ± 19 mg NO3 − l − 1, ± standard deviation between farms). The water inflows calculated ranged from 86 to 190 mm depending on the year for the 4-month drainage period. The amounts of N leached were on average 23% lower in OF (12.5 ± 2.9 kg N ha − 1 yr − 1 ) than in CF systems (16.2 ± 6.3 kg N ha − 1 yr − 1 ). Concerning farming practices, the main impacting factors were the use of EOM in fall, the lack of catch crops before spring, and the proportion of legumes in the rotation. Overall, this wide collaborative network highlights good and innovative practices by CF and OF farmers attempting to decrease NO3 − in groundwater. Highlights: N leaching must be evaluated on the rotation term. On average, organic farming showed 23% less nitrate leaching than conventional farming. N harvested was not significantly different between organic and conventional systems.